2019
DOI: 10.18805/ijar.b-1072
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor activity analysis based on habitat, season and time of the day in Polish Konik horses from reserve breeding using the Global Positioning System (GPS)

Abstract: The aim of the present study was to analyze the locomotor activity of horses living under near-natural conditions using the Global Positioning System (GPS). The study was conducted on the pack of 15 Polish Konik horses in 2018. Three habitats (forest, meadows and hay), two seasons (winter and spring) and four times of the day were distinguished. Significant effects of habitat (p less than 0.0000) and time of the day (p less than 0.0000) on locomotor activity were found. In addition, a significant influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…So far, knowledge on horses' locomotion in grasslands is mainly based on observations or has, more recently, been derived from GPS studies on feral horses in extensive landscapes such as large rangelands [27,29,36], where the search for forage and water, the escape from danger and social interactions are its main drivers [30,37]. Domestic horses' locomotion and grazing behaviour, by contrast, are restricted in time and space by the applied management practices.…”
Section: Locomotion Behaviour Of Horses On Pasturementioning
confidence: 99%
“…So far, knowledge on horses' locomotion in grasslands is mainly based on observations or has, more recently, been derived from GPS studies on feral horses in extensive landscapes such as large rangelands [27,29,36], where the search for forage and water, the escape from danger and social interactions are its main drivers [30,37]. Domestic horses' locomotion and grazing behaviour, by contrast, are restricted in time and space by the applied management practices.…”
Section: Locomotion Behaviour Of Horses On Pasturementioning
confidence: 99%
“…The hours between 11 p.m. to 4 a.m. were expected to be the main resting phase, as in Northern Germany in June this period coincides with the absence of day light, however, this resting phase could very precisely be reproduced by the analysis of hourly contact networks. These findings were backed completely by [ 26 ], who showed that the travelled mean distances were smallest between 11 p.m. to 4 a.m.…”
Section: Discussionmentioning
confidence: 80%
“…Important work has been carried out on the walked distances of feral horses, stating averaged distances varying from 3.5 km per day [ 23 ] to 9 km per day [ 24 ] to 15.9 km per day [ 25 ]. In [ 26 ] it was distinguished between Konik horses’ walking distances in the forest (6.5 km per day) and the meadow (2.6 km per day). With [ 27 ] a recently published study reports the walked daily distances of a large, inhomogeneous group of domestic horses to be 8.43 km.…”
Section: Introductionmentioning
confidence: 99%
“…2B). The 87 Sr/ 86 Sr values from the first molars (0.71032 and 0.71005) are documented nearby on the Sambia Peninsula ( 59 ) and southern Poland ( 62 ) and may represent trading or raiding with neighboring groups or the seasonal home range of a feral horse of this stature ( 63 ). Migration period horses from Tumiany show even greater mobility, with five horses identified as nonlocal (Fig.…”
Section: Resultsmentioning
confidence: 99%